The Present Day Situation on Standard Albanian and the Theory of Argumentation about it - Mantho, Edlira (Investigationes Linguisticae, 2009)
The primary goal of this article is to examine the strand that connects Albanians of all regions: the standardization of the Albanian language. The Albanian language, which allows for identification, protection, development and the conception of our union as a nation, is being transformed into an instrument of division, not only separating Albanians into Ghegs and Tosks, but also according to political borders. Recently, an argument in Kosovo has emerged demanding that standard Albanian not be used at all. This argument itself is comprised of several sub-currents distinguished by their specific views on standardization. The various positions are as follows: 1. The standard language must not change. 2. The standard language must be revised. 3. Two standards must be adopted. 4. The standard language should be avoided as it is a product of the violence of a communist dictatorship. 5. A new language, with a different name, should be created. We contend that language evolves and the act of selection is up to its speakers, irrespective of what has been predetermined. Changes to the standard language are necessary, but by no means must they impinge upon the systematic character of the standard. The changes must be made when the language itself suggests them and must not result from violence or short-sightedness. Standard Albanian will continue to be the common language of both Albanians and Kosovar Albanians. Furthermore, by sharing a common language and a common linguistic history, Albanians will have a prosperous future.